The Epithelial Cell Glycocalyx in Ocular Surface Infection - Argüeso, Pablo; Woodward, Ashley M.; AbuSamra, Dina B. (Frontiers in Immunology, 2021)
The glycocalyx is the main component of the transcellular barrier located at the interface between the ocular surface epithelia and the external environment. This barrier extends up to 500 nm from the plasma membrane and projects into the tear fluid bathing the surface of the eye. Under homeostatic conditions, defense molecules in the glycocalyx, such as transmembrane mucins, resist infection. However, many pathogenic microorganisms have evolved to exploit components of the glycocalyx in order to gain access to epithelial cells and consequently exert deleterious effects. This manuscript reviews the implications of the ocular surface epithelial glycocalyx to bacterial, viral, fungal and parasitic infection. Moreover, it presents some ongoing controversies surrounding the functional relevance of the epithelial glycocalyx to ocular infectious disease.